COMPREHENSIVE ASSESSMENT SERVICES OF PUBLIC TRANSPORT - O Y Efimova (RUDN Journal of Economics, 2015)
Building a comprehensive assessment of urban passenger transport services represents the cumulative interest parametric both in terms of passenger and the carrier. The ratio of high-quality components of the services provided consumer demand reveals their correspondence to each other. A certain number of indicators of quality of public transport, resulting due to the functioning of on-board satellite navigation is considered in the same scale, and is being transformed per 1 ths. Km. Rationing quantitative quality indicators with different units of measurement, eliminates distortion of the result by the use of coefficients from 0 to 1. The significance of each parameter is determined by the correlation analysis without the involvement of the expert opinion. Application of the method can be carried out at the level of the route, road transport companies and urban passenger system as a whole and create an evaluation algorithm for the quality of urban passenger transport.